Research on ion cyclotron emission driven by deuterium–deuterium fusion-produced tritium ions on the Experimental Advanced Superconducting Tokamak - Huapeng Zhang; Lunan Liu; Wei Zhang; Xuan Sun; Xinjun Zhang; Zhengshuyan Wang; Zelin Xu; Jiadong Zhang; Weijian Qin; Liuxin Li; Yuhao Jiang; Sichun Qiu; et al. (Nuclear Fusion)
In the 2023 experiment campaign, we measured ion cyclotron emission (ICE) signals on the Experimental Advanced Superconducting Tokamak (EAST), edge ICE excited by tritium ions. A fusion product derived from the deuterium–deuterium (D−D) fusion reaction, whose spectral peak matches the fundamental cyclotron frequency of the tritium ions ( ω _CT ) in the plasma edge near the last closed flux surface, was observed using the ion cyclotron range of frequency (ICRF) antenna-based diagnostic system at the plasma boundary on the low field side in the EAST. In this study, we present the first observation of ICE with frequency matching at the plasma boundary. The excitation position of ICE is approximately R = 2.29 m on EAST, and we find that ICE is easier to excite below a certain threshold of plasma radiation. To investigate the excitation mechanism of ICE, we obtained the tritium ion distribution via the TRANSP/Fusion Products Model code and used it to explain the excitation mechanism of ICE. The given distribution has a bump-on tail structure in the energy direction and anisotropy in the pitch angle direction. In addition, we explain why high-energy tritium ions can reach and accumulate at the plasma boundary. It is important to study ICE because ICE can help distinguish the species of fusion-product ions, which can also help monitor the fusion alpha ions in large fusion devices, such as CFETR, DEMO, and ITER.